PSYCHOLOGICAL-PEDAGOGICAL BASIS OF FORMING A PEDAGOGICAL CULTURE OF LISTENING IN THE TRAINING OF FUTURE MUSIC TEACHERS - Пащенко, М.І.; Осауленко, Л. (SWorldJournal, 2025)
The article explores the concept of pedagogical culture, the features of a future teacher of music who would perform his work professionally. The technology of mastering the art of listening by a future teacher of music is proposed. The difficulties that